Evaluation of Bioavailable Contents of Arsenic, Copper and Zinc in Some Poultry Farms Soils in Osun State, Nigeria - Ogunwale, Taiwo Olusegun; Oyekunle, John Adekunle O.; Ogunfowokan, Aderemi Okunola; Oyetola, Simeon Oyesoji (Industrial and Domestic Waste Management, 2022)
This work evaluated the mobility and bioavailability of arsenic, copper and zinc in chosen poultry farmlands situated within Osun State, Nigeria in respect to the soil physicochemical characteristics. The site was split into 12 zones of about equal sites. Soil samples were collected over a period of four months from each zone for analysis of soil physicochemical characteristics and As, Cu and Zn contents in sequential fraction of the soil sample. Sequential fractionation of soil samples were conducted utilizing reworked Tessier technique, utilizing Flame Atomic Absorption Spectrophotometer. Mean of total content (mg/kg) and percentage bioavailability were: As 470.48±48 (31.16%), Cu 62.95±10.61 (29.02%) and Zn 125.58±20.74 (26.67%), respectively. Analysis of variance and correlation analyzes indicated that soil pH, % clay, % organic carbon, cation exchange capacity, and metal speciation in soil control metal mobility and bioavailability in the poultry farm soil. The mean contents of As, Cu and Zn in soil in the sampling area were usually more than those of the control site, indicating some degrees of contamination of the poultry farm soil by these metals. Also, the mean contents of As in some zones were considerably greater (p